Disclosure of errors and apology: law and ethics - Westrick, Susan J.; Jacob, Nyshi (JNP-Journal for Nurse Practitioners, 2016)
Error disclosure and apology are evolving concerns for advanced practice nurses who have increased exposure to liability. Error disclosure is required by regulatory agencies and the American Nurses Association Code of Ethics for Nurses, yet barriers to disclosure exist and nurse practitioners may not be aware of state apology laws that protect some statements from use in civil lawsuits for negligence or malpractice. Two law cases that apply apology laws are reviewed to illustrate these protections. Best practices for error disclosure are presented, and nurse educators are urged to include error disclosure content in nurse practitioner curricula as part of safety and quality education.
5 citations (Crossref) [2023-10-31] tex.eissn: 1878-058X tex.unique-id: ISI:000369613500021
Keywords: dept.nur